An investigation into the ability of non-IFRS earnings measures' to predict future operating cash flows for a sample of South African JSE listed companies - Chittenden, Reece (College of Accounting, 2019)
This study investigates whether or not non-IFRS earnings measures can predict future operating cash flows. Many companies consistently present non-IFRS earnings measures, being voluntarily disclosed earnings measures lacking in formal definition, in order to communicate a companies’ core or sustainable earnings. Prior research into the usefulness of non-IFRS earnings measures has shown mixed results around the measures’ ability to predict a company’s future stock returns. Furthermore, there is some evidence that non-IFRS earnings measures have been used opportunistically to report a more favourable financial performance compared to IFRS earnings, questioning the usefulness and relevance of non-IFRS earnings measures. A linear mixed model was used to investigate the ability of non-IFRS earnings measures’ to predict future operating cash flows [CF(T+1)] using the top 40 Johannesburg Stock Exchange (JSE) companies over the sample period from 2012 to 2016. The results of the statistical analysis showed that the non-IFRS earnings measure within the final model showed a positive and significant relationship with CF(T+1), which aligns with findings of a similar Australian study. Further to this, the inclusion of an indicator variable for mining companies was found to improve the model’s ability to predict future operating cash flows using non-IFRS earnings measures. The results of this study add to the growing area of research surrounding non-IFRS measures by uniquely focusing on South African companies, with similar results to prior studies. These findings may be of assistance to analysts and investors for valuation purposes and to standard-setting bodies for consideration as part of their current research project on performance reporting. Finally, the results provide justification for non-IFRS earnings measures as valid and useful metrics for analysis of company performance.